MARKETING OF AGRICULTURAL PRODUCTS IN THE INTERNATIONAL MARKET AND EXCHANGE POLICIES UNDER THE LAWS OF THE WORLD TRADE ORGANIZATION - Hadi Yahya Saleh Mareeh; Adhita Sri Prabakusuma; Rami Abdullah Aleryani (Socio-Economics/Agribusiness Department, 2021)
What has been observed in the developing countries' economy is the dominance of hydrocarbons over exports which have reached 98% in recent years. This may have bad consequences in case oil prices collapse of fuel prices, taking into account that these are related to political, economic, and social variables occurring in the world. Besides, hydrocarbons are vital, yet they are on the way to disappearing. The agricultural sector is one of the most important ones that developing owns, and that is required to develop its way and means of production, which contributes to the development of Middle East countries exports outside hydrocarbon. The most important products are dates, olives, citrus, potatoes, tomatoes, carrots, grapes, and apricots. These products are considered the most important products that can contribute to the development of exports outside hydrocarbons.